Family bonding and self-concept: An indirect effect mediated by school experiences among students - Ishak, Z.; Chew, F.P. (2012)
School experiences, family bonding and self-concept had always been a crucial factor in influencing all aspects of a student’s development. The purpose of this study is to develop and to validate a priori model of self-concept among students. The study was tested empirically using Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA) to validate the structural model. To address these concerns, 1167 students were randomly selected and utilized the Cognitive Psycho-Social University of Malaya instrument (2009).Resulted demonstrated there is indirect effect from family bonding to self-concept through school experiences among secondary school students as a mediator. Besides school experiences, there is a direct effect from family bonding to self-concept and family bonding to school experiences among students.